IDENTIFIKASI HEWAN INVERTEBRATA PADA FILUM MOLUSKA DI PESISIR PANTAI KENJERAN SURABAYA - Anggita Shafira; Ni’matur Rohma; Prestiani; Pramita Laksitarahmi Isrianto (Prodi Biologi Universitas PGRI Ronggolawe, 2024)
One way to identify an object is to make observations to a place to find objects that will be examined, in this article we take invertebrate animal objects in the mollusca phylum on Kenjeran Beach Surabaya. Phylum mollusca are a group of soft-bodied and invertebrate animals with shell-protected bodies. Data collection was carried out using exploration and observation methods, with research data analysis techniques using descriptive analysis techniques. 5 species of mollusca were obtained on the Kenjeran Coast, namely sea snails (Bolinus brandaris), Hiatella arctica, Sorgenfreispira brachystoma, Eupleura caudata and Keoang mas (Pomacea canaliculate). The existence of this study aims to recognize invertebrate animals in the mollusk phylum and the important characteristics of the species we found there.